Interactions between larvae of the threatened saproxylic beetle Osmoderma eremita and other flower chafers in Mediterranean woodlands: implications for conservation - Chiari, Stefano; Zauli, Agnese; Audisio, Paolo; Carpaneto, Giuseppe M (Insect Conservation and Diversity, 2014)
* Interactions between larvae of one of the most charismatic and threatened saproxylic beetles, Osmoderma eremita (Scopoli, 1763), and other flower chafer species (Coleoptera: Scarabaeidae) were investigated by taking samples of wood mould, i.e. loose material inside the cavity, from 151 living hollow trees in two Mediterranean woodlands during August 2010. * Multi-species occupancy models estimate low occupancy probabilities for both O. eremita (ψ ± SE = 0.36 ± 0.13) and other flower chafer species (0.42 ± 0.06), which showed similar microhabitat requirements without competing. * In cavities where larvae of both groups were present, the probability of detecting O. eremita during the sieving of 2 l of wood mould was not affected by whether larvae of other flower chafers occur in the same sample and vice versa. * Unexpectedly, larvae of O. eremita were detected with a higher probability when larvae of other flower chafers occurred in the cavity. * Model selection statistics strongly support that increasing the sampled volume of wood mould increases the probability of detecting larvae, especially for O. eremita. * Wood mould sampling resulted in a reliable method for detecting the presence of O. eremita larvae, but further studies are needed to investigate the potential damage caused by this procedure in the fragile microhabitat of tree cavities. * To preserve populations of O. eremita and other flower chafers, management actions should be focused on increasing the density of hollow trees and the volume of tree cavities by favouring the natural ageing of trees and by creating artificial habitats in living trees.
Keywords: co-occurrence; detectability; hollow trees; monitoring; occupancy; PRESENCE; Scarabaeidae; wood mould sampling

Dispersal patterns of a saproxylic beetle, Osmoderma eremita, in Mediterranean woodlands - Chiari, Stefano; Carpaneto, Giuseppe M.; Zauli, Agnese; Zirpoli, Giancarlo M.; Audisio, Paolo; Ranius, Thomas (Insect Conservation and Diversity, 2012)
* Dispersal patterns of a beetle inhabiting tree hollows, Osmoderma eremita (Scopoli, 1763) (Coleoptera: Cetoniidae), were studied in a cork oak (Quercus suber) woodland in central Italy, the southernmost part of its distribution range. During 2 years, we used radio telemetry to monitor dispersal of 39 free-ranging individuals (16 males, 23 females). * Telemetered beetles spent their lifetime not only inside hollow trees but also in other habitats, such as above or under the ground surface. * Beetles were more active at the beginning of the season. Eighty-one per cent of the males and 69% of the females conducted dispersals during their lifetime. * The dispersal distance over individuals' lifetime did not differ between sexes. The longest dispersal was conducted by a female that moved 1504 m. Thirty-nine per cent of dispersing individuals reached distances farther than 250 m. Both dispersal rate and range are higher than what has been found in Northern Europe. * The population size per tree is low, most of the adults leave their natal tree, and a high predation rate (at least 28%) was observed among dispersing beetles. Therefore, to balance the local extinction risk from single trees, a high density of hollow trees is probably required. It is desirable that suitable trees are concentrated at a spatial scale of a few hundred metres.
Keywords: Coleoptera; dispersal; habitat colonisation; hollow trees; radio tracking; Scarabaeidae

Habitat of an endangered saproxylic beetle, Osmoderma eremita, in Mediterranean woodlands - Chiari, Stefano; Carpaneto, Giuseppe M.; Zauli, Agnese; Marini, Lorenzo; Audisio, Paolo; Ranius, Thomas (ECOSCIENCE, 2012)
The habitat of Osmoderma eremita, a European endangered beetle species restricted to tree cavities, was examined in central Italy, at the southernmost limit of its distributional range. The occurrence of adults, larvae, and fragments was investigated in 170 and 151 living hollow trees by pitfall trapping and sampling of wood mould (i.e., loose material) in the hollow, respectively. Overall, O. eremita was present in 22% of the trees, which belonged to 4 different tree species (Ostrya carpinifolia, Quercus suber, Acer obtusatum, and Quercus pubescens). The frequency of presence was higher in cavities with more than 4 L of wood mould, in cavities with dry or half-moist wood mould rather than wet wood mould, and with wood mould with low soil contamination. A comparison with northern regions indicated that the warmer macro-climatic conditions in the south make the species independent of a warm microclimate. As most of the hollow trees contain only a small amount of wood mould (<4 L), the habitat quality is generally poorer than in oak pastures studied in northern Europe.
The following values have no corresponding Zotero field: pub-location: PAVILLON CHARLES-EUGENE MARCHAND, LOCAL 0166, ST FOY, QUEBEC G1K 7P4, CANADA publisher: UNIVERSITE LAVAL
Keywords: Coleoptera Scarabaeidae; conservation; hollow trees; microclimate; pitfall traps; wood mould

Surveying an endangered saproxylic beetle, Osmoderma eremita, in Mediterranean woodlands: a comparison between different capture methods - Chiari, Stefano; Zauli, Agnese; Mazziotta, Adriano; Luiselli, Luca; Audisio, Paolo; Carpaneto, Giuseppe M. (Journal of Insect Conservation, 2012)
Measuring population size is riddled with dif- ﬁculties for wildlife biologists and managers, and in the case of rare species, it is sometimes practically impossible to estimate abundance, whereas estimation of occupancy is possible. Furthermore, obtaining reliable population size estimates is not straightforward, as different sampling techniques can give misleading results. A mark-recapture study of the endangered saproxylic beetle Osmoderma eremita was performed in central Italy by applying four independent capture methods within a study area where 116 hollow trees were randomly selected to set traps. Detection probability and population size estimates were drawn from each of these four capture methods. There were strong differences in detection probability among methods. Despite using pheromone and beetle manipulation, capture histories were not affected by trap-happiness or trapshyness. Population size estimates varied considerably in both abundance and precision by capture method. A number of 0.5 and 0.2 adult beetles per tree was estimated using the whole data set by closed and open population models, respectively. Pitfall trap appeared the optimal method to detect the occurrence of this species. Since in the southern part of its distribution range, a single population of O. eremita is widespread in the landscape, and includes beetles from more than one hollow tree, conservation efforts should focus not only on preserving few and isolated monumental hollow trees, but should be extended to large stands.
Keywords: Coleoptera Scarabaeidae; conservation; Dead Wood; occupancy; Population size estimates; Sex pheromone